Negatively charged phospholipids doped liposome delivery system for mRNA with high transfection efficiency and low cytotoxicity - Lin Wang; Huanchun Xing; Shuai Guo; Wenbin Cao; Zinan Zhang; Lijuan Huang; Sui Xin; Yuan Luo; Yongan Wang; Jun Yang (Taylor & Francis Group, 2023)
AbstractMessenger RNA (mRNA) has become one of the most potential drugs in recent years. However, efficient and safe delivery of fragile and easily degradable mRNA is a major challenge. Appropriate delivery system (DS) determines the final effect of mRNA. Cationic lipids play a crucial and decisive role in the entire DS, but also cause huge biosafety problems due to the high toxicity. In this study, a new DS for mRNA delivery that combines negatively charged phospholipids was developed in order to neutralize the positive charge and thus increase the safety. Further, the factors affecting mRNA transfection from cell to animal were investigated. The mRNA DS with optimum condition of lipid composition, proportions, structure, and transfection time was synthesized. Adding an appropriate amount of the anionic lipid to liposomes could increase the safety while maintaining the original transfection efficiency. For transporting mRNA in vivo, requirements regarding the mRNA encapsulation and releasing rate should be further considered to optimize DS design and preparation.